Perceptions of the sitio 117 and San Gabriel settlers on the legitimacy of their land possession vis-a-vis the existence of UP in Mindanao - Ebrado, Donde Aries
This study aims to determine the perceptions of the settlers on the status of their land ownership, find out the arguments of legitimacy of both the settlers and the university, determine the history of the land ownership of the two communities, determine how the settlers of the two sitios were able to acquire the lands they are presently occupying, discuss the role of the Board of Liquidators to claim of the settlers, discuss in brief the land ownership crisis between the settlers might want to have with the UP in Mindanao Administration. In depth self-structured interview with the respondents was done on purpose, the target respondents were the old settlers of the community. There were twenty respondents for the study, ten from each community. Formal interview sessions were done fro two consecutive weeks. It was found out in the study that the conflict on land ownership with a government agency is not actually new for them as they have already encountered the same nature of a case with the Bureau of Plant Industry (BPI) in the 1960's and 1970's. However, before the case with the BPI was settled,there came in the University of the Philippines in Mindanao who have gained legal ownership of the land through Presidential Proclamation 822. It was found out that the settlers perceived that they legitimate own the land because they have existed in the area since 1950's. They were first to occupy the land they have applied ownership of the land through the Board of Liquidators(BOL), and they have a land title to show as theirs. On the other hand, aside from the proclamation, the university has had a memorandum of agreement with the BOL which in effects presents the nullification of the prior application of the settlers to the BOL and leaves the university the right to transfer/relocate the settlers.